KEMAMPUAN WAJIB PAJAK ORANG PRIBADI DALAM MENGGUNAKAN E-FILING - Andi Andi (Jurnal Ekonomi-Qu, 2018)
This research aimed to investigate the factors that influenced perceived usefulness, perceived satisfaction, perceived ease, perceived the security and privacy, readiness technology tax payers information to use toward the intention taxpayers in using e-filing in KPP Pratama Serang. This research used primary data obtained from questionnaires. The sample used were the taxpayer registered in the Tax Office Serang that using e-filing. The sampling techniqueused was purposive sampling. Of the 150 questionnaires distributed, the number of questionnaires returned was 130 questionnaires. The analytical method used is the analysis of Structural Equation Modeling (SEM). The data were processed using software Smart Partial Least Square (SmartPLS) version 3. The results of this study revealed that all the independent variables in this study, perceived usefulness, perceived satisfaction, perceived ease, perceived security and privacy, readiness technology tax payers information significant effect on theinterest of individual taxpayers in the use of e-filing.